Experiencing powerful English through cacalla - Castillo, Emma S. (Philippine Journal of Linguistics, 2003)
English is not a native language in our country, yet there is great desire to learn it. The language has continued to perplex us as to the ways by which we can achieve competence in it. There has been much research directed towards the "best" practices in teaching and learning English. Sadly, the research has not yielded convincing results. The ambition that most Filipinos have is not really to be native speakers of English but to learn it because it is a language of wider communication (LWC) not only here in the Philippines, but globally as well. In addition, much of what there is to learn about almost anything academic is written in English. To access that kind of knowledge, therefore, one has to learn English, not to mention the non-utilitarian or non-instrumental aims in learning English; for example, one may want to learn a language in order to communicate effectively with native speakers of that language, i.e., an integrative aim. Many Filipinos, particularly those aiming to go and live abroad, say, in the United States, may have such an integrative reason, albeit this may not sound patriotic in some sense. A new framework (CA CALLA) of teaching a language is being proposed. Details of that framework will be presented. A recent achievement in the Philippines with respect to evolving this model is its application in textbook writing. A new series whose publication is forthcoming adopts the CA CALLA framework. The paper will describe the framework as adopted in said textbook series.